Controlled release of bovine serum albumin from stimuli‐sensitive silk sericin based interpenetrating polymer network hydrogels. Issue 8 (3rd January 2013) - Wu, Wen; Wang, Dongsheng; Lian, Yuan
Abstract: In recent years, the use of stimuli‐sensitive interpenetrating polymer network (IPN) hydrogels for the encapsulation and controlled release of protein drugs has received significant attention. The purpose of the present study was to investigate the release of bovine serum albumin (BSA), a model drug, from a series of thermosensitive silk sericin (SS) poly( N ‐isopropylacrylamide) and pH‐responsive SS poly(methacrylic acid) IPN hydrogels. The effect of the chemical architecture of the IPN was investigated on the percentage loading of BSA and its subsequent release from the loaded devices. The temperature and pH of the release medium were studied for their impact on the release of BSA. The pulsatile releasing behavior of IPN hydrogels revealed that they can be made into microcapsules or thermo‐valves, which act as an on–off release control. © 2013 Society of Chemical Industry Abstract : In this study, a series of thermosensitive SS‐PNI and pH‐responsive SS‐PMAA IPN hydrogels were used as durg carrier and the release profile of BSA from these IPN hydrogels was investigated. The results showed that the release amounts depended on the component of the IPN hydrogels and temperature/pH which enables the hydrogels to be used as an oral delivery system for protein drugs.